Splinting for the non‐operative management of developmental dysplasia of the hip (DDH) in children under six months of age - Dwan, K; Kirkham, J; Paton, R; Morley, E; Newton, A; Perry, D (Wiley, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To determine the role of splinting and the optimal treatment strategy for the non-operative management of DDH in children under six months of age. To identify if there are particular subgroups of patients for whom the optimal management strategy may differ.